Rapid spread of diseases in Caribbean coral reefs - Goreau, Thomas J. (1998)
The variety and frequency of diseased coral reef organisms has increased across the Caribbean during the last 10 years. Black band, white band, white pox, and white plague diseases have become more widespread. Yellow band disease now affects a major portion of Montastrea annularis across the Caribbean. Mortality of Yellow band disease-affected tissues was observed to increase in the southern Caribbean during early 1997 , with affected tissue turning white and dying. During the past two years a major fraction of encristing red calcareous Porolithon algae died across the Caribbean. This disease, also found in the Indian Ocean, lacks the orange band characteristic of Pacific coralline lethal orange disease. A millimeter thick white circular rim is seen between live tissue and dead skeleton. Numerous other emerging diseases have attacked many other organisms in this period, including gorgonians, sponges, and echinoderms. Many of those now known have not yet been described. Generally, most diseases affect one or few species (except white plague and black band diseases); and their spatial and temporal distributions appear unrelated to bleaching, pollution (except black band disease), sedimentation, or grazing. This paper brings together observations made separately by many researchers over a large area and long period; in order to evaluate the geographic and historical distributions of each disease: Photographic images are included which show diagnostic field criteria for recognizing each disease.